Agronomic performance and morphogenic and structural characteristics of Axonopus aureus pastures under phosphate fertilization levels in the Roraima’s savannas (Research, Society and Development, 2023)
The effect of phosphate fertilization (0, 30, 60 and 120 kg of P2O5 ha-1) on forage production and morphogenetic and structural characteristics of Axonopus aureus was evaluated under natural field conditions in the savannas of Roraima. Phosphate fertilization positively and significantly (P